2005
DOI: 10.1289/ehp.7562
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure to Ultrafine Particles and Oxidative DNA Damage

Abstract: Exposure to ultrafine particles (UFPs) from vehicle exhaust has been related to risk of cardiovascular and pulmonary disease and cancer, even though exposure assessment is difficult. We studied personal exposure in terms of number concentrations of UFPs in the breathing zone, using portable instruments in six 18-hr periods in 15 healthy nonsmoking subjects. Exposure contrasts of outdoor pollution were achieved by bicycling in traffic for 5 days and in the laboratory for 1 day. Oxidative DNA damage was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
126
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(138 citation statements)
references
References 52 publications
10
126
1
1
Order By: Relevance
“…However, a high correlation between wind speed and mixing height meant that we could not estimate the independent effects of these two variables. Regardless, our findings are consistent with those of Vinzents et al (2005) who also observed a significant inverse relationship between temperature and wind speed and UFP exposures while bicycling in traffic. However, we were unable to identify other studies exploring the effects of ambient temperature and wind speed on UFP exposures in transportation environments.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, a high correlation between wind speed and mixing height meant that we could not estimate the independent effects of these two variables. Regardless, our findings are consistent with those of Vinzents et al (2005) who also observed a significant inverse relationship between temperature and wind speed and UFP exposures while bicycling in traffic. However, we were unable to identify other studies exploring the effects of ambient temperature and wind speed on UFP exposures in transportation environments.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the exposure levels reported in this investigation must be interpreted with caution as they are likely conservative estimates of actual exposures in transportation environments. Nevertheless, the majority of particles produced by gasoline and diesel vehicles are between 0.02 and 0.1 mm in diameter (Morawska and Zhang, 2002), and previous studies employing P-TRAKs have observed significant associations between UFP counts and oxidative DNA damage (Vinzents et al, 2005) as well as changes in heart rate variability (Chan et al, 2004) and vasoconstriction (Rundell et al, 2007). Therefore, while the P-TRAK is not the most sensitive instrument available, it remains a valuable instrument in environmental epidemiology owing to its portability and relatively low cost.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, variations in peak expiratory flow rates were more strongly associated with ambient UFP concentrations in one of these studies relative to larger particles (Pekkanen et al, 1997). Recently, UFP exposures were shown to contribute to oxidative DNA damage in healthy adults, with indoor exposures contributing most to cumulative exposure levels owing to the large amount of time people spend indoors (Vinzents et al, 2005). Therefore, future populationbased studies interested in the respiratory effects of UFPs may need to include indoor measures of UFP exposure to capture an accurate depiction of cumulative exposure profiles.…”
Section: Introductionmentioning
confidence: 83%
“…Ultrafine particles may originate outdoors, from vehicle emissions and gas-to-particle conversions (Levy et al, 2003;Vigotti et al, 2007). However, indoor UFP originate from a wide range of indoor sources and occupant-related activities such as cooking, smoking, cleaning, and painting (Wallace et al, 2002;Vinzents et al, 2005;Weichenthal et al, 2007). One of the potential approaches to control indoor air pollutant concentrations is to reduce emission sources (Oliveira Fernandes et al, 2008).…”
mentioning
confidence: 99%